2022
DOI: 10.1039/d2cp03822f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast charge transfer in a nonfullerene all-small-molecule organic solar cell: a nonadiabatic dynamics simulation with optimally tuned range-separated functional

Abstract: Herein, we have employed LR-TDDFT-based nonadiabatic dynamics simulations to investigate the ultrafast charge transfer in a nonfullerene all-small-molecule donor-acceptor (D-A) system formed by a porphyrin small-molecule donor ZnP and a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 100 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…322−324 The combination of the OT-RSH functional and NAMD method was used to investigate the ultrafast charge transfer in a nonfullerene allsmall-molecule donor−acceptor system formed by a porphyrin small-molecule donor ZnP and a recently developed nonfullerene small-molecule acceptor 6TIC. 325 Our results indicated that the obtained results are less sensitive to the selected range separated hybrid functionals used for optimization. Moreover, such methods can provide even more reasonable results compared to the untuned ones.…”
Section: Transition Metal Complexes and Soc Effectsmentioning
confidence: 72%
See 1 more Smart Citation
“…322−324 The combination of the OT-RSH functional and NAMD method was used to investigate the ultrafast charge transfer in a nonfullerene allsmall-molecule donor−acceptor system formed by a porphyrin small-molecule donor ZnP and a recently developed nonfullerene small-molecule acceptor 6TIC. 325 Our results indicated that the obtained results are less sensitive to the selected range separated hybrid functionals used for optimization. Moreover, such methods can provide even more reasonable results compared to the untuned ones.…”
Section: Transition Metal Complexes and Soc Effectsmentioning
confidence: 72%
“…The OT-RSH method depends on the nonempirical optimization of the range-separation parameter ω in the range-separated functionals so that a fundamental property that the exact functional must obey in exact Kohn–Sham (KS) or generalized KS (GKS) theory is fulfilled: that is, for an N-electron system, the negative of the HOMO energy − ε HOMO (N) must be equal to the molecular vertical IP­(N). Thus, these OT-RSH functionals can predict the excited state properties of various molecular systems effectively, and have witnessed great successes in fields ranging from OSCs to thermally activated delayed fluorescence (TADFs). The combination of the OT-RSH functional and NAMD method was used to investigate the ultrafast charge transfer in a nonfullerene all-small-molecule donor–acceptor system formed by a porphyrin small-molecule donor ZnP and a recently developed nonfullerene small-molecule acceptor 6TIC . Our results indicated that the obtained results are less sensitive to the selected range separated hybrid functionals used for optimization.…”
Section: Applicationsmentioning
confidence: 87%
“…Therefore, the NAMD simulations in this work were performed with classical path approximation, which has been demonstrated to work very well for describing excited-state relaxation without involving large conformational change and bond forming or -breaking. 84,86,87,[91][92][93] Since ZnPc-PDI dyads exhibit rigid structures and no bond forming or breaking is involved as suggested by previous experimental work, 74 the classical path approximation is very suitable for this system.…”
Section: Simulation Detailsmentioning
confidence: 98%
“…This Considering the significant differences in results between the gas phase and benzonitrile, it is crucial to further validate the reliability of the excited state calculation method adopting the OT-SRSH-PCM functional used in this work. While previous studies have shown that tuning the o parameter can provide accurate results for the gas phase, [59][60][61][62][63]74 we decided to perform more tests to demonstrate the importance of tuning the b parameter for the calculations in benzonitrile. To this end, we conducted two additional excited state calculations using the same structure, the same PCM solvent model using benzonitrile as the solvent, and functional, but different o and b parameters.…”
Section: Pccp Papermentioning
confidence: 99%
See 1 more Smart Citation